Perkembangan Lifestyle Dan Sosial Media Marketing Terhadap Keputusan Pembelian Brand Erigo - Dwi Mega Aprilia; Herlinda Maya Kumala Sari; Rita Ambarwati Sukmono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research was conducted to determine the influence of lifestyle, brand awareness, and social media marketing on Le Minerale purchasing decisions. The main problem in this research is that the Top Brand Index value of the Erigo brand is ranked third, with many competitors. This research uses a quantitative method, descriptive research type and uses a random sampling method with a sample size of 96 respondents. This research uses data collection techniques using questionnaires. The data analysis technique used in this research is multiple linear regression analysis using SPSS statistical tools. Based on the results of research and discussions that have been carried out and described, it can be concluded that lifestyle, brand awareness and social media marketing influence the decision to purchase Erigo Lbrnd. Keywords: Lifestyle, Awaneres Brand, Social Media Marketing, Purchasing Decisions, Erigo Brand